2009
DOI: 10.1111/j.1365-2249.2009.03981.x
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated inflammatory response of primary human myeloid dendritic cells to lipopolysaccharide in patients with inflammatory bowel disease

Abstract: SummaryInflammatory bowel disease (IBD) results from a breakdown of tolerance towards the indigenous flora in genetically susceptible hosts. Failure of dendritic cells (DC) to interpret molecular microbial patterns appropriately when directing innate and adaptive immune responses is conceivable. Primary (conventional, non-monocyte generated) CD1c necrosis factor (TNF)-a and interleukin (IL)-8. Toll-like receptor (TLR)-4 expression by mDC was higher inremission and increased significantly in flaring UC and CD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 64 publications
5
55
0
3
Order By: Relevance
“…Therefore, dysregulated function of innate immune cells that are responsible for phagocytosis of ACs (efferocytosis), such as macrophages and dendritic cells (DCs), could augment IBD pathogenesis. Intriguingly, IBD patients display higher frequencies of DCs positive for several activation and maturation markers in the lamina propria of inflamed colon tissues, and IBD DCs produce significantly more proinflammatory cytokines than DCs from healthy controls (11)(12)(13). Although these studies indicate that DCs have a function in IBD pathogenesis, their role in the inflammatory cascade leading to intestinal inflammation, and its association with AC clearance, has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, dysregulated function of innate immune cells that are responsible for phagocytosis of ACs (efferocytosis), such as macrophages and dendritic cells (DCs), could augment IBD pathogenesis. Intriguingly, IBD patients display higher frequencies of DCs positive for several activation and maturation markers in the lamina propria of inflamed colon tissues, and IBD DCs produce significantly more proinflammatory cytokines than DCs from healthy controls (11)(12)(13). Although these studies indicate that DCs have a function in IBD pathogenesis, their role in the inflammatory cascade leading to intestinal inflammation, and its association with AC clearance, has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 89%
“…The number of DCs expressing the maturation markers CD80, CD83, CD86 and CD40 is elevated in CD and UC [102][103][104][105]. DCs express also higher levels of TLR2 and TLR4 [102] and accordingly, show exaggerated response to LPS in IBD [106]. This may result in false recognition of commensal bacteria and induction of pro-inflammatory immune responses.…”
Section: Immune Dysregulationmentioning
confidence: 99%
“…Co-expression of CD103 was found on approximately 4% of the cells. A similar population was identified by Baumgart et al [35] as being CD14 -CD19 -CD11c + CD1c + . It is difficult to know if these cells correspond to migratory or tissue resident phagocytes since they express the migratory molecule CCR7 but few express CD103.…”
Section: Phagocyte Subsets In the Human Intestinementioning
confidence: 56%
“…Consistent with this, Ng et al [54] showed that DCs from patients with Crohn's Disease express more IL-12p40 and IL6 compared to healthy controls. Finally, LPS stimulation of mucosal DCs in Crohn's Disease patients induced high secretion of TNFα and IL-8 [35]. For macrophages, it has been shown that CD14 + intestinal macrophages from patients with Crohn's Disease produced abundant IL-23 and TNF-α in response to stimulation with commensal bacteria [32].…”
Section: Phagocyte Subsets In the Intestine Of Patients With Crohn's mentioning
confidence: 99%